Eco color doppler evaluation of renal hemodynamic in the prognosis of acute heart failuree. (14th October 2021) - Turrini, F; Galassi, M; Sacchi, A; Ricco', B; Messora, R; Bertolotti, M; Pinelli, G; ,
Abstract: Background: Elevation of right atrial pressure is a typical feature of acute heart failure (AHF), it is transmitted to renal veins leading to persistent kidney congestion. We aimed to evaluate the role of Doppler ultrasound in monitoring kidney congestion during diuretic therapy. Methods: 71 patients (26 F - mean age 80.8±8.2 - mean EF 0.40±13.2) admitted for AHF underwent cardiac and renal Echo Doppler examination at day 1–3–5 of Hospital stay. Parameters of arterial and venous flow within cortical right kidney were recorded. Venous Doppler Profile (VDP) was classified as: continuous (C), pulsatile (P), biphasic (B) or monophasic (M) according to the growing degree of derangement. Arterial resistive index (RI) >0.8 was considered elevated. Correlation between renal hemodynamic changes and clinical outcome (Death and cardiovascular (CV) hospitalization) at 60 days was sought. Outcome: VDP derangement (M or B) was detected in 57 patients (80.3%) at day 1 and in 36 at day 5 (52.2%, p <0.05). RI was elevated in 43 patients (61.4%) at day 1 and in 28 patients at day 5 (43.8%, p<0.05). Patients with deranged VDP on admission, had higher pulmonary artery sistolic pressure (PASP) (53±10 vs 39±17 mmHg, p<0.05) but similar EF, BNP and GFR values. Patients with elevated RI on admission exhibited lower GFR (47.6±23.8 vs 60.7±19.1 ml/min/1.73 m 2, p<0.05) but similar EF, BNP and PASP values. At day 5, 41 (57.7%) patients had VDP improved of at least one class or continuous VDP (Table 1). After 60 days, 13 (18.3%) patients died and 8 (11.3%) had a CV hospitalization. Kaplan Meier analysis found a significant better outcome in those patients whose VDP did improve after diuretic therapy (Log Rank test p<0.05 – Figure 1). Conclusions: Most patients admitted with AHF present deranged VDP. Diuretic treatment lead to VDP improvement and to renal RI decrease. In this perspective study, for the first time VDP improvement after endovenous diuretic treatment resulted associated to reduced risk of death and CV Hospitalization. Evaluation of VDP could become a useful tool in monitoring the efficacy of diuretic treatment in AHF. Funding Acknowledgement: Type of funding sources: None.